2018
DOI: 10.13189/ojdom.2018.060202
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Regular and White MTA and A Grey Portland Cement in Human Dental Pulp Cells

Abstract: Currently many materials have been used with pulpotomies in primary teeth. These include MTA, that as a direct pulp capping material seemed to stimulate natural dentin repair at pulpal exposure sites. The composition of this product is based on Portland cement. Later, white MTA was introduced as an esthetic improvement over the original material (grey MTA). A number of studies have been performed on this new material to determine if it shows the same properties as gray MTA. The biocompatibility of MTA has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…This proved that MTA has high biocompatibility, which can be well tolerated by body tissue compared to self-adhesive resin cement. 10,11 These results are in accordance with a study conducted by Lillo et al 22 and Solanki et al, 23 which reported the biocompatibility of MTA in human cells. In addition, another study reported that the 12-week observation of animal tissue in vitro and in vivo exhibited normal cell growth and no infection.…”
Section: Discussionsupporting
confidence: 91%
“…This proved that MTA has high biocompatibility, which can be well tolerated by body tissue compared to self-adhesive resin cement. 10,11 These results are in accordance with a study conducted by Lillo et al 22 and Solanki et al, 23 which reported the biocompatibility of MTA in human cells. In addition, another study reported that the 12-week observation of animal tissue in vitro and in vivo exhibited normal cell growth and no infection.…”
Section: Discussionsupporting
confidence: 91%